2008
DOI: 10.1071/sh07047
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV and other sexually transmissible infections in relation to lemon or lime juice douching among female sex workers in Jos, Nigeria

Abstract: There were no significant associations between the prevalence of STI and HIV and lime or lemon juice usage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 20 publications
0
16
1
Order By: Relevance
“…Lack of hygiene, promiscuity, non-use of condoms, the existence of genital tract lesions and high-risk practices during sexual intercourse are factors that promote the transmission of STIs and HIV [1] [6] [12] [13]. Our rate of 50.4% is higher than those of Reed [11] in Indonesia and Wang [10] in China, which were 39% and 41% respectively.…”
Section: Prevalence Of Genital Infectionscontrasting
confidence: 40%
“…Lack of hygiene, promiscuity, non-use of condoms, the existence of genital tract lesions and high-risk practices during sexual intercourse are factors that promote the transmission of STIs and HIV [1] [6] [12] [13]. Our rate of 50.4% is higher than those of Reed [11] in Indonesia and Wang [10] in China, which were 39% and 41% respectively.…”
Section: Prevalence Of Genital Infectionscontrasting
confidence: 40%
“…Studies on the prevalence of HIV among female sex workers in some parts of Nigeria revealed increasing rates of 17.5% in 1991 to 35.6% in 1995. Recently, Imade and coworkers [10] in Jos found an alarmingly higher prevalence of 48% among 398 female sex workers.…”
Section: Introductionmentioning
confidence: 99%
“…The state has a population of 3,206,531 (National Bureau of Statistics, 2006) and consists of people from all works of life. HIV infection prevalence reports in Plateau state surveys have ranged from of 4.88% in the general populations, with most of the infected people younger than 40 years and a significantly higher prevalence in females than males (Gomwalk et al, 2012), to 8.2% in pregnant women (Sagay et al, 2005) and 48% in commercial sex workers (Imade et al, 2008). The state is well known for tourism and usually attracts a high influx of visitors.…”
Section: Methodsmentioning
confidence: 99%